Analysis of Return on Asset, Net Profit Margin, Debt to Equity Ratio, on Stock Prices of Financial - Mari Ananda; Fitri Diana Gulo; Mohd. Nawi Purba; Wenny Anggeresia Ginting (Kusuma Negara Business School, 2023)
This research aims to analyze the Return On Assets, Net Profit Margin, and Debt to Equity Ratio, and their impact on the Stock Prices of Financial Sector Banking Companies listed on the Indonesia Stock Exchange for the period 2016 – 2021. This study uses purposive sampling techniques based on secondary data and is classified as explanatory research, with a quantitative approach. The research sample consists of 37 banking companies, which are part of a total population of 46 banking companies. Multiple Linear Regression Analysis is used to test the hypothesis in this study. The test results indicate that, partially, Return On Assets (X1) significantly affects the Stock Prices of banking companies, while the other two independent variables, namely, Net Profit Margin (X2) and Debt to Equity Ratio (X3), do not significantly affect the Stock Prices. However, simultaneously, the variables of Return On Assets, Net Profit Margin, and Debt to Equity Ratio have been proven to have a positive effect on the Stock Prices of Financial Sector Banking Companies listed on the Indonesia Stock Exchange during the period 2016-2021.